Effects of Rest-Break Intention on Rest-Break Frequency and Work-Related Fatigue. (March 2017) - Blasche, Gerhard; Pasalic, Sanja; Bauböck, Verena-Maria; Haluza, Daniela; Schoberberger, Rudolf
Objectives: The present paper presents findings from two studies addressing the effects of the employee's intention to have rest breaks on rest-break frequency and the change of well-being during a workday. Background: Rest breaks are effective in avoiding an accumulation of fatigue during work. However, little is known about individual differences in rest-break behavior. Method: In Study 1, the association between rest-break intention and the daily number of rest breaks recorded over 4 consecutive workdays was determined by generalized linear model in a sample of employees ( n = 111, 59% females). In Study 2, professional geriatric nurses ( n = 95 females) who worked over two consecutive 12-hour day shifts recorded well-being (fatigue, distress, effort motivation) at the beginning and the end of their shifts. The effect of rest-break intention on the change of well-being was determined by multilevel modeling. Results: Rest-break intention was positively associated with the frequency of rest breaks (Study 1) and reduced the increase of fatigue and distress over the workday (Study 2). Conclusion: The results indicate that individual differences account for the number of breaks an employee takes and, as a consequence, for variations in the work-related fatigue and distress. Application: Strengthening rest-break intentions may help to increase rest-break behavior to avoid the buildup of fatigue and distress over a workday.